Assessing the Intensity of Economic Progress, Industrialization,Energy Use on Environmental Degradation - Hossain, M D Akter; Eleais, M D; Urbee, Afrida Jinnurain; Hasan, M D Atik; Tahrim, Farian (South Asian Journal of Social Sciences and Humanities, 2024)
This study intensifies the interrelationship between environmental downfall, economic and industrial enhancement, renewable and non-renewable energy consumption in the period of 1997 to 2018 for the G-7 and selected five MENA countries. The paper intends to explore how renewable energy, fossil fuel, electricity generation, GDP, and industrialization affect the environmental pollution. For a dynamic panel data analysis, some statistical methods have been utilized, including Slope Homogeneity (SH), Cross Section Dependence (CSD), Cross-Section Im-Pesaran-Shin (CIPS), and Cross-Section Augmented Dickey-Fuller (CADF) of the second generation unit root tests, and the second generation (Westerlund-2007) CO-integration test, both Feasible Generalized Least Squares (FGLS), Panel-Corrected Standard Error (PCSE), and dynamic generalized method of moments (d-GMM) panel estimation approach have been applied. Feasible generalized least square (FGLS) shows that if GDP, fossil fuel energy consumption, industrialization, and electricity generation, increase by 1% then CO2 emission increases by 79.8%, 5.3%, 10.37%, and 8.26% respectively. If renewable energy increases by 1% CO2 emission decreases by 6.56%. When GDP growth rises, there is a corresponding increase in environmental pollution within industrialized economies. This demonstrates a positive correlation between GDP, industrialization, and CO2 emissions, which means that as the economy grows, environmental degradation will continue to worsen over time. Therefore, concerned parties should take proper policy steps to protect environment in industries and towards sustainable growth.
Keywords: CO2 emission; Renewable Energy; Fossil Fuel; Industrialization; Electricity generation